2001
DOI: 10.1177/152660280100800615
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Angioplasty in the Treatment of Chronic Femoropopliteal Arterial Occlusions: Preliminary Experience

Abstract: Vibrational angioplasty using coronary guidewires seems to be a promising ancillary technique in the management of chronic femoropopliteal arterial occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In cases where CTO crossing with standard guidewires was unsuccessful after 5 min of continuous attempt, patients were then enrolled in the trial and treated with the Wingman catheter (Reflow Medical, San Clemente, CA) prior to endovascular revascularization. The time period for attempted crossing with a standard guidewire was based off of precedent set by previous crossing catheter trials (usually 3 min in previous trials) 4,5,9‐17 ) . The Wingman catheter is an over‐the‐wire crossing catheter available in 0.014‐, 0.018‐, and 0.035‐in.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where CTO crossing with standard guidewires was unsuccessful after 5 min of continuous attempt, patients were then enrolled in the trial and treated with the Wingman catheter (Reflow Medical, San Clemente, CA) prior to endovascular revascularization. The time period for attempted crossing with a standard guidewire was based off of precedent set by previous crossing catheter trials (usually 3 min in previous trials) 4,5,9‐17 ) . The Wingman catheter is an over‐the‐wire crossing catheter available in 0.014‐, 0.018‐, and 0.035‐in.…”
Section: Methodsmentioning
confidence: 99%
“…The primary endpoints of the trial were statistically compared to performance goals that were calculated based on results from other CTO crossing catheters 4,5,9‐17 . Study success required the lower one‐sided 95% confidence limit of the primary efficacy endpoint to exceed 70.7%, which was derived assuming an 83.2% crossing rate and a 12.5% margin.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate intraluminal crossing of chronic total occlusions, we also used vibrational angioplasty in a subcohort of our patients (18). This is a method that uses a specially designed hand-held motorized device that produces vibrational motion to a 0.014 or 0.018 guide wire (1921). Once the lesions were successfully crossed, our treatment strategy consisted of direct stenting of lesions prone to peripheral embolization, such as occlusions or complex stenoses in the aortoiliac axis and acute occlusions in the femoropopliteal region and primary balloon angioplasty of below-the-knee lesions (17,18,22).…”
Section: Methodsmentioning
confidence: 99%
“…The thermal laser angioplasty has been proved to be effective, with successful recanalization of the superficial femoral artery in 80% of cases and a primary patency rate of 50% at 1 year 32 . It has also been suggested that vibrational angioplasty, using coronary equipment, improves the recanalization rate in long chronic femoral occlusions with a 100% technical success rate and acceptable patency at 9 months 33 . Moreover, an interesting and promising technique seems to be cryoplasty; the angioplasty balloon is inflated with pressurized liquid nitrous oxide which cools to a temperature of −10°, freezing the plaque and inducing apoptosis.…”
Section: Chronic Critical Arterial Ischemiamentioning
confidence: 99%